A contextual account of the generation effect: A three-factor theory - McDaniel, Mark A; Waddill, Paula J; Einstein, Gilles O (Journal of memory and language, 1988)
Recent studies have shown that the generation effect (items generated by an individual are better remembered than items that are read) can be diminished or eliminated under between-subjects deployment of the encoding task (generating vs. reading). Three experiments that further delineate the nature of the generation effect in between-subjects designs are reported. Experiments 1 and 2, using a structured word list, found significant generation effects in free recall under certain cue-target conditions and written-response conditions. Generation effects in recognition and cued recall occurred in all conditions. In Experiment 3, with intentional learning instructions, significant generation effects were not obtained. Current accounts of recent failures to find significant generation effects are discussed in light of our results, and all are found lacking to some degree. We propose an extension to the idea that generation enhances both cue-target relational processing and individual-item processing; namely, in some contexts generation will enhance whole-list processing.